Alberto III Pio, Baldassarre Peruzzi e la Sagra di Carpi: la messa in scena del Medioevo - Franzoni, Claudio (Opus Incertum, 2022)
Alberto III Pio (1475-1531), prince of Carpi and leading man of politics and culture at the beginning of the sixteenth century, entrusted Baldassarre Peruzzi with the project for a new cathedral in the Emilian town. The previous building (the “Sagra”) was not demolished but shortened and completed with a new façade designed by Peruzzi. The new façade contained three new inscriptions, two of which quoted medieval inscriptions from the “Sagra” itself, and one taken from the old Romanesque portals which was reused and placed in the center of the new façade. The intention of the prince was to combine Peruzzi’s new and modern architectural style with the existing medieval forms, themselves visible proof of the Catholic faith of past centuries: the Christian tradition that a few years later Alberto will try to defend in the controversy against Erasmus of Rotterdam.